ANALISIS PERAN KARYAWAN DALAM HUBUNGAN ANTARA DUKUNGAN PIMPINAN DENGAN FEKTIVITAS SPIP DAN KUALITAS LAPORAN KEUANGAN - Sudarno, Sudarno (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
The implication of issuance of Law No. 17/ 2003 on State Finance and Law No 71/ 2010 onGovernment Accounting Standard (SAP), the state universities have to compile and present finansial statements. The purposes of this research are to investigate factors which are affectingthe quality of finansial statement, the role of effectiveness SPIP to the effect of and to identify thecharacteristic of develop a finansial statement and level of leadership supported at state highereducation in Jawa Tengah and DI Yogyakarta. Population of this research was the accountingdivision responsible for preparing financial statements in 15 state universities in Jawa Tengahand DI Yogyakarta. Assuming each division had 7 staff; questionnaires were distributed by postsand couriers to 105 staff. Data from 67 respondents (63,81%) were analyzed by path analysis byusing PLS 2.0. This study supported the role of efectivness SPIP in developing a high quality offinansial statement. The commitment and motivation affects to quality of finansial statementindirectly through efectivness SPIP. However, this research has not enough evidence to said thatcompetency affects to efectivness SPIP. The other, The results of this study tend to supportmediation hypothesis that leadership supported affects to efectivness SPIP and quality offinansial statement indirectly through competency, commitment and motivation.